27.9k views
1 vote
Simplify as far as possible.

1
3cos (180° + x)sin (360° - X)
sin (360° + x)cos (180° - x)​

User Omilus
by
4.9k points

1 Answer

4 votes

Answer:

See below

Explanation:

cos (180 + x) = - cos x

sin (360 + x) = sin x

sin 360 - x) = -sin x

cos (180 - x) = - cos x

3cos (180° + x)sin (360° - X) = -3cos x (- sin x) = 3 cosx sinx

sin (360° + x)cos (180° - x)​ = sin x (- cos x) = -sinx cosx

3cos (180° + x)sin (360° - X)sin (360° + x)cos (180° - x)​

= 3 cosx sinx (-sinx cosx) = -3 (sin x)^2 (cos x)^2

I am not sure what the question really is, but hopefully the above can steer you in the right direction.

User Cadriel
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.